Small and medium enterprises (SMEs) disrupt food systems to deliver healthy diets to urban consumers: Twiga case study, Nairobi, Kenya - Chege, Christine Gacheri Kiria; Onyango, Kevin Omondi; Lundy, Mark M.; Kabach, Joram (2023)
Micro Small and Medium-Enterprises (MSMEs) in many developing countries play an important role in the agri-food systems. They provide employment opportunities as well as source of foods for urban consumers. In Kenya, the MSMEs provide an interesting disruption in the rapidly growing traditional markets. Efficient sourcing of foodstuffs is one of the challenges faced by MSME food vendors in Nairobi. Traditionally small-scale food vendors travel by informal buses to wholesale wet markets several times a week to source limited volumes of fresh fruit and vegetables. These early morning trips generate additional costs including bus fare, relatively high unit costs for small volumes of purchases, insecurity, and opportunity costs for mostly female vendors. Twiga Foods, a Kenya agritech and logistics private company formed in 2014, seeks to resolve some of these issue through the efficient sorting and distribution of fresh produce in urban Kenya to reduce fragmentation in the produce market (Cook & O'Neill, 2020). It employs a cashless mobile-based business-to-business (B2B) food supply (fruits and vegetables) platform that connects farmers to small and medium-sized vendors, outlets and kiosks, and the main aim is to address the problem of food flow from farmers to markets in urban areas across Kenya (Cook & O'Neill, 2020; von Bismarck-Osten, 2021). What can the Twiga Foods case teach us about the potential of a disintermediation model in the LMIC food system to provide multiple benefits in terms of food and nutrition security, incomes, employment, and potential spill-over effects?